Carbon literacy - can simple interventions help? Effect of information provision on emissions knowledge of private households - Kretschmer, Sandra (2022)
Keywords: Carbon literacy; Information provision; Low-carbon behaviour; Emissions knowledge; Climate change

Carbon literacy – Can simple interventions help? Effect of information provision on emissions knowledge of private households - Kretschmer, Sandra (Energy Policy, 2024)
Understanding public perceptions of various carbon abatement behaviours and how these can be influenced with informational interventions is an essential prerequisite to encourage low-carbon behaviour. By means of a survey experiment among a representative sample of 1492 German households, I evaluate individual carbon literacy, i.e. the ability to perceive the carbon emissions associated with individual actions, based on a ranking task of abatement behaviours. Using two treatment interventions, I test whether simple information provision in the form of a ranking of the most carbon-intense household actions or a heuristic for carbon intensities can correct misperceptions and thus increase carbon literacy. The results show that Germans severely underestimate the abatement potential of reduced meat consumption, avoiding food waste, and to a lesser extent of not driving a car, while they overestimate the potential of recycling and avoiding plastic bags. While the heuristic fails to increase carbon literacy, the ranking does so by a significant amount. In particular, it corrects the perceptions of the top mitigating actions. However, the severe underestimation of a vegetarian diet and avoiding food waste persists. This indicates that especially the underestimation of food-related emissions is deep-rooted.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Carbon literacy; Climate change; Emissions knowledge; Information provision; Low-carbon behaviour

Green innovations: The organizational setup of pilot projects and its influence on consumer perceptions - Grimm, Veronika; Kretschmer, Sandra; Mehl, Simon (Energy Policy, 2020)
Pilot-, test- and demonstration-projects (PTDs) are a prominent policy tool to promote the adoption of smart, green technologies. However, as technology adoption is heavily dependent on the individual attributes and beliefs of potential adopters, it is important to understand the influence of a PTD's organizational setup on technology perception. By varying the information about a PTD's organizational setup in a survey experiment among a selected sample of potential PTD-participants, we gather first experimental evidence for the effect of different setups on the perception of green technologies. We show that the organizational setup has a significant impact on a product's perceived contribution to the energy transition, its establishment in the market, cost-reduction potential, innovativeness and environmental friendliness. In particular, full organizational cooperation between government, university and industry consistently improves perceptions compared to a partial setup. Regarding the willingness to participate in a PTD, we find that communication and support are the most imperative aspects and even more important than economic benefits. Our findings provide policy-makers with a more ample foundation on how PTDs should be designed to successfully transfer technologies to the marke
Keywords: Pilot projects; Organizational setup; Adoption decision; Triple helix; Innovation diffusion

Home energy storage: A characterization of potential adopters in Germany - Grimm, Veronika; Kretschmer, Sandra; Mehl, Simon (2018)

Market design for renewable energy auctions: An analysis of alternative auction formats - Bichler, Martin; Grimm, Veronika; Kretschmer, Sandra; Sutterer, Paul (Energy Economics, 2020)
Auctions are widely used to determine the remuneration for renewable energies. They typically induce a high concentration of renewable energy plants at very productive sites far-off the main load centres, leading to an inefficient allocation as transmission line capacities are restricted but not considered in the allocation, resulting in an inefficient system configuration in the long run. To counteract these tendencies effectively, we propose a combinatorial auction design that allows to implement regional target capacities, provides a simple pricing rule and maintains a high level of competition between bidders by permitting package bids. By means of extensive numerical experiments we evaluate the combinatorial auction as compared to three further RES auction designs, the current German nationwide auction design, a simple nationwide auction, and regional auctions. We find that if bidders benefit from high enough economies of scale, the combinatorial auction design implements system-optimal target capacities without increasing the average remuneration per kWh as compared to the current German auction design. The prices resulting from the combinatorial auction are linear and anonymous for each region whenever possible, while minimal personalised markups on the linear prices are applied only when necessary. We show that realistic problem sizes can be solved in seconds, even though the problem is computationally har
Keywords: Renewable energy auction; Combinatorial auction; Market design